Coordination Polymer Framework Based On‐Chip Micro‐Supercapacitors with AC Line‐Filtering Performance. Issue 14 (7th March 2017) - Yang, Chongqing; Schellhammer, Karl Sebastian; Ortmann, Frank; Sun, Sai; Dong, Renhao; Karakus, Melike; Mics, Zoltán; Löffler, Markus; Zhang, Fan; Zhuang, Xiaodong; Cánovas, Enrique; Cuniberti, Gianaurelio; et al.
Abstract: On‐chip micro‐supercapacitors (MSCs) are important Si‐compatible power‐source backups for miniaturized electronics. Despite their tremendous advantages, current on‐chip MSCs require harsh processing conditions and typically perform like resistors when filtering ripples from alternating current (AC). Herein, we demonstrated a facile layer‐by‐layer method towards on‐chip MSCs based on an azulene‐bridged coordination polymer framework (PiCBA). Owing to the good carrier mobility (5×10 −3  cm 2  V −1  s −1 ) of PiCBA, the permanent dipole moment of azulene skeleton, and ultralow band gap of PiCBA, the fabricated MSCs delivered high specific capacitances of up to 34.1 F cm −3 at 50 mV s −1 and a high volumetric power density of 1323 W cm −3 . Most importantly, such MCSs exhibited AC line‐filtering performance (−73° at 120 Hz) with a short resistance–capacitance constant of circa 0.83 ms. Abstract : On‐chip micro‐supercapacitors based on an azulene‐bridged coordination polymer framework are prepared by a facile layer‐by‐layer approach. The as‐fabricated on‐chip micro‐supercapacitors deliver high specific capacitances, specific volumetric power, and energy densities as well as promising AC line‐filtering performance with an extremely short RC time.